DETERMINATION OF AGE OF CORAL REEFS ON PANIKIANG ISLAND, BARRU DISTRICT, SPERMONDE ISLANDS THROUGH MEASUREMENT ACTIVITY 14C USING LSC (LIQUID SCINTILLATION COUNTING) METHOD - Arisandi Arisandi; Alfian Noor; Maming Maming (Marina Chimica Acta, 2019)
Determination Of Age Of Coral Reefs On Panikiang Island, Barru District, Spermonde Islands Through Measurement Activity 14C Using LSC (Liquid Scintillation Counting) Method. This research was using a sample of coral reefs taken from the Panikiang Island, Barru, Spermonde Islands. This research has been carried out by using sample preparation with physic and chemical. Sample preparation was done physically and chemically. Chemical preparation was carried out by using a mixture of NaOH with 30% H2O2 followed by a mixture of HClO4 with 30% H2O2, and finally with HCl solution to produce a clean sample with a weight reduction of 7.94%. Absorption of CO2 through reaction with HCl 10% and NH4OH as Carbosorb .produced K2CO3. The total carbon in the sample solution is 0.2496 gram sobtained through titration method.  Radiocarbon dating method based on the measurement of the specific activity of the samples obtained from the results of counts LSC (Liquid Scintilation Counter) Hidex 300 SL.The specific activity of coral sample is 14.68 ± 4.04 DPM/gC. Age of coral sample which were calculated from the specific activity were 342.04 ± 37.66 years.